Standardization and Quality Control of the Herbal Medicine Mist Nibima, Employed to Treat Malaria and COVID-19, Using Physicochemical and Organoleptic Parameters and Quantification of Chemical Markers via UHPLC-MS/MS - Emmanuel Kofi Kumatia; Francis Ofosu-Koranteng; Alfred Ampomah Appiah; Kofi Bobi Barimah (International Journal of Analytical Chemistry)
Mist Nibima is an essential herbal medicine used to treat malaria, bacterial, yeast, and COVID-19 infections. However, the drug has not been standardized and its active chemical ingredients are also not known. This study employed physicochemical, organoleptic, qualitative, and quantitate phytochemical analysis to established standards for Mist Nibima. Additionally, UHPLC was used to quantify the alkaloid cryptolepine in the drug using calibration curve. The chemical ingredients in Mist Nibima were thereafter characterized using UHPLC-MS. Organoleptic evaluation shows that Mist Nibima is a very bitter, cloudy, broom yellow decoction with the following physicochemical parameters: pH = 6.10 ± 0.08 (at 28.3°C), total solid residue = 5.34 ± 0.27%w/v, and specific gravity = 1.0099 ± 0.0000. The total alkaloid (23.71 ± 1.311%) content of the drug is 3 times its total saponins (7.993 ± 0.067%) content. Methyl cryptolepinoate (37.10%), cryptolepine (33.56%), quindoline (20.78%), 11-isopropylcryptolepine (5.16%), and hydroxycryptolepine (3.14%) were the active chemical ingredients in the drug with the concentrations of 18.64 ± 0.255, 16.85 ± 0.231, 10.42 ± 0.143, 2.56 ± 0.034, and 1.70 ± 0.023 µg/mL, respectively. Administration of a single oral therapeutic dose (30 mL) of Mist Nibima corresponds to ingestion of 559.2 ± 7.662, 505.5 ± 6.930, 312.6 ± 4.285, 76.8 ± 1.028, and 51.0 ± 0.699 µg of methyl cryptolepinoate, cryptolepine, quindoline, 11-isopropylcryptolepine, and hydroxycryptolepine, respectively. This translates into a corresponding daily dose of 1677.6 ± 22.986, 1516.5 ± 20.790, 937.8 ± 12.855, 230.4 ± 3.084, and 153.0 ± 2.097 µg of methyl cryptolepinoate, cryptolepine, quindoline, 11-isopropylcryptolepine, and hydroxycryptolepine. These results could now serve as tools for authentication, standardization, and quality control of Mist Nibima to ensure its chemical and pharmacological consistency and safety.